HUBUNGAN KEMAMPUAN BERSOSIALISASI DENGAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 9 BEKASI - Juwita Damayanti (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2016)
This research is quantitative which aims to determine whether there iscorrelation between the students’ social ability and students' motivation, especially in theeighth grade of SMP Negeri 9 Bekasi in academic year 2013-2014.The purpose of this study is to investigate whether there is correlation between the students’social ability and students' motivation, especially in VIII-14 class at SMP Negeri 9 Bekasi.The calculation of questionnaire or test research used the Cronbach alpha reliability as acommon measure of internal consistency of multi-item scale, the numbers in the range of0.70 (acceptable), 0.80 (good) and the Likert scale questionnaire to measure the attitudes,opinions and perceptions of a person's or a group of events or social phenomena. Eachanswer is connected with the form of a statement or gesture of support expressed in wordsstrongly agree (SS), agree (S), disagree (D), strongly disagree (STS). From these results, 32items were obtained which can be used for the study of the 60 problems that exist.The population of the research was all eighth grade students of SMP Negeri 9 Bekasi inacademic year 2013-2014 consists of 960 students. Then, 30 students were taken as a sample.The sampling technique used was Probability Sampling, it is a sampling technique thatprovides equal opportunity for every element (member) to be elected as members of thepopulation sample. Collecting data in this research was using an open questionnaire for itsvariables.Based on this research, it is proved that the hypothesis can be accepted. There is a significantcorrelation between social ability and learning motivation at VIII-14 class of SMP Negeri 9Bekasi. With the test calculations r count r 0.941 while table at significant level of 0.05% hasa mean value of 0.361 count r> r table, then Ho is rejected and Ha accepted. Then proceedusing the t-test analysis, with the final result obtained results t-count table 2.048 14.773 ofusing a significant level of 5%.23The conclusion that can be concluded from this research is that there is correlation betweensocial skills and learning motivation at VIII-14 class of SMP Negeri 9 Bekasi.Bibliography: 23 (2001-2012). Keywords: social skills and motivation to study.